1995
DOI: 10.1111/j.1476-5381.1995.tb13239.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of delayed rectifier K+‐current by levcromakalim in single intestinal smooth muscle cells: effects of cations and dependence on K+‐flux

Abstract: 1 Whole-cell voltage-clamp recordings were made from single smooth muscle cells isolated from the longitudinal layer of the guinea-pig small intestine.2 Levcromakalim ((-)Ckm) inhibited delayed rectifier K-current (IK(DR)) and induced a voltageindependent K-current (IK(Ckm)). Both effects were inhibited similarly by glibenclamide. In some cells, however, IK(-ckm) could be induced without any effect on IK(DR)-3 Ba2" caused a voltage-dependent block of IK(dckm). The IC50 was 0.2 mM at -40 mV (6 cells), but at 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…On the other hand, they do not beyond all doubts disprove this hypothesis, either. Altogether, the data published on this matter are so far controversial; while Ashcroft et al (1994) studying mouse pancreatic islet cells in the whole-cell configuration could not at all establish inhibition of K v by the K + channel opener, diazoxide, inhibition of K v by levcromakalim was found in our experiments (guinea pig portal vein, single channels in cell-attached patches), in those of Edwards et al (1993;rat portal vein, whole-cell configuration), and in most of the guinea pig intestinal cells studied by McHugh and Beech (1995; whole-cell clamp configuration). In the latter study however, in a number of cells, no inhibition of K v by levcromakalim was observed.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…On the other hand, they do not beyond all doubts disprove this hypothesis, either. Altogether, the data published on this matter are so far controversial; while Ashcroft et al (1994) studying mouse pancreatic islet cells in the whole-cell configuration could not at all establish inhibition of K v by the K + channel opener, diazoxide, inhibition of K v by levcromakalim was found in our experiments (guinea pig portal vein, single channels in cell-attached patches), in those of Edwards et al (1993;rat portal vein, whole-cell configuration), and in most of the guinea pig intestinal cells studied by McHugh and Beech (1995; whole-cell clamp configuration). In the latter study however, in a number of cells, no inhibition of K v by levcromakalim was observed.…”
Section: Discussioncontrasting
confidence: 61%
“…glibenclamide, Zn 2+ , Ba 2+ , and Rb + , also reversed the effect of levcromakalim on K v . Based on these latter findings, McHugh and Beech (1995) suggested that competition for the same submembraneous reservoir of K + ions might explain the matching of K + membrane currents before and during the presence of the KCO, thereby abandoning the idea of levcromakalim affecting the K v directly or via an intermediate protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IK v has been characterized in various types of smooth muscle cells, e.g., coronary artery (14), trachea (6,10), portal vein (18) and pulmonary artery smooth muscle cells (19,20,24,27). Delayed rectifier K + channels are pharmacologically blocked by 4-aminopyridine (22), tedisamil (21) and cromakalim (9,15,4). Naturally occurring inhibitors of smooth muscle K v are intracellular Mg 2+ , Ca 2+ (11) and protein kinase C (2).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium channel openers relax various gastrointestinal smooth muscles including ileum [7,8], stomach [9,10], and colon [11]. They have also been shown to activate glibenclamide-sensitive K + currents in single cells from colon [11] and ileum [12]. Recently the potassium channel opener cromakalim has been shown to possess antiulcer activity in various experimental gastroduodenal ulcer models [13].…”
Section: Introductionmentioning
confidence: 99%